Effects of Innovative Monitoring and Evaluation Strategies on Project Performance: A Case of Solid Waste Management Project, Juba City Council, South Sudan - Dimitry, Loro Edward (Daystar University, School of Applied Human Sciences, 2024)
Project monitoring and evaluation plays a crucial role in project performance. Innovative monitoring and evaluation strategies have become increasingly important in recent years, with many organizations considering their uptake. Solid waste management refers to source separation, storage, collection, transportation, and disposal of waste in an environmentally sustainable manner. This study sought to evaluate the effects of innovative monitoring and evaluation strategies on project performance of the solid waste management project in Juba City Council, South Sudan. The study objectives were to establish the innovative monitoring and evaluation strategies employed in solid waste management projects; assess the performance of solid waste management projects; and evaluate the effects of innovative monitoring and evaluation strategies on project performance. This study was anchored on results-based management theory and theory of change. Results-based management approach theory is a widely used monitoring and evaluation strategy that focuses on achieving measurable results while the theory of change is a planning and evaluation framework that is used to map out the causal pathways that lead from inputs to desired outcomes. The study employed a descriptive survey research design. The population of the research study comprised 2,000 staff working in Juba City Council. This research employed a census approach, entailing the collection of data from every member of the study population. The study’s target population comprised 66 staff of the Juba City Council solid waste management project. Data was collected using a semi-structured questionnaire that included both open-ended and closed-ended questions. A pretest was conducted to ensure the validity and reliability of the questionnaire. The Statistical Package for the Social Sciences (SPSS), version 21, was used to analyze the data. Both descriptive and inferential statistics were presented in tables. The results showed a significant relationship between innovative monitoring and evaluation strategies and project performance (F-statistic = 27.965, Sig. .002). Stakeholder engagement improved decision-making, enhanced accountability, and increased transparency as key benefits. The study underscored the critical role of innovative monitoring and evaluation strategies in achieving successful solid waste management by facilitating better decision-making, promoting accountability and transparency, and enabling adaptive management practices based on real-time data. The study concluded that innovative monitoring and evaluation strategies significantly enhance the performance of the Juba City Council's solid waste management project. Furthermore, the recommendations presented align with Sustainable Development Goal 11 (sustainable cities and communities) and Sustainable Development Goal 3 (good health and well-being), as well as South Sudan's development agenda and Vision 2040. Future research and initiatives could build upon this study’s foundation by exploring impactful and cost-effective innovative monitoring and evaluation approaches for diverse contexts. Investigating the integration of new technologies and data analytics into monitoring and evaluation practices holds significant promise for further optimization. Developing clear guidelines for implementing innovative monitoring and evaluation in solid waste management can also contribute to broader adoption and success. This demonstrates the potential of innovative monitoring and evaluation strategies to contribute to broader societal goals of environmental sustainability, public health, and economic development.
Master of Arts in Monitoring and Evaluation
Keywords: Project monitoring and evaluation